Tahap pengetahuan keselamatan dan kesihatan pekerjaan di kalangan pekerja di makmal perubatan di Lembah Klang - Anuar I.; Zahedi F.; Kadir A; Mokhtar A B (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : A safety culture practice through prevention needs skillful, knowledgeable and competencies workers. The effectiveness of occupational safety and health programme implementation needs the knowledge related to Occupational Safety and Health Acts, 1994 (OSHA 1994) and its regulations. Objective : This study was to determine the level of knowledge and awareness towards Occupational Safety and Health (OSH) aspects among workers in medical laboratory. Methodology : A cross-sectional study was carried out on 34 medical laboratories in which 17 were from private and another 17 laboratories were from public sectors. It consists of 112 medical laboratory disciplines. Data were obtained using self-administered questionnaire consisting of 33 questions related to Occupational Safety and Health (OSH). Each question was coded “know” and “do not know” and respondents were needed to state their understanding towards each OSH issue tendered. Results : Respondent’s level of knowledge was analyzed according to socio-demography and socioeconomic factors. OSH level of knowledge among medical laboratory workers showed that there are significant differences (p<0.05) according to factor of age, educational level and their position in organization. In contrary, there are no significant differences (p>0.05) in OSH knowledge according to between sex, marital status, income and services sectors among workers in medical laboratories. Only about 60.5% of respondents knew the existence of OSHA 1994, whereas those who knew about OSHA 1994 regulations were below than 50.0% from overall respondents. Conclusion : Promotion and practices of dynamic safety culture through prevention needs high knowledge of OSH.